Characterization of the tacaco (Sechium tacaco) production system in Cartago, Costa Rica - Monge-Pérez, José Eladio (2025)
The objective of the work was to carry out a characterization of the tacaco (Sechium tacaco) production system.  The research was carried out in the cantons of Paraíso and Alvarado, province of Cartago, Costa Rica, between September 2021 and December 2022.  15 semi-structured interviews were conducted with tacaco growers on various topics related to the production system of this vegetable.  Data was obtained on:  planting, staking, planting time, pruning and leaf removal, fertilization, pest and disease control, irrigation, crop rotation and association, harvest, post-harvest, and marketing.  It is concluded that the production of tacaco is in the hands of small growers, who have an important cultural heritage related to the production of this vegetable.  This work constitutes the first study on the characterization of the tacaco production system in Costa Rica.